2016
DOI: 10.1016/j.addma.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of adenosine triphosphate bioluminescence for assessing the cleanliness of additive-manufacturing materials used in medical applications

Abstract: Additive Manufacturing (AM) is widely gaining popularity as an alternative manufacturing technique for complex and customized parts. AM materials are used for various medical applications in both metal and polymer options. Adenosine Triphosphate (ATP) bioluminescence technology is a rapid, user-friendly method of quantifying surface cleanliness and was used in this study to gather quantitative data on levels of contamination on AM materials at three different stage processes: post build, post cleaning and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Specifically, sand blasted parts display surfaces with impregnated blast media in the form of AlO x elements -Al ions in the outer oxide layer of Ti-6Al-4V have been shown to reduce the oxide stability and increase the likelihood of Al ion dissolution [191,192] . Electropolishing and chemical etching can lead to the formation of micropits, increasing oxygen infiltration, as well as destabilize the native oxide layer, reducing corrosion resistance [191,195] . Conversely, Longhitano et al investigated the combination of various finishing processes on SLM Ti-6Al-4V, and found that blasting followed by chemical etching produced parts with and R a of approximately 4 µm -this can be explained by the stepwise action of blasting removing material from the surface, and subsequent etching removing blast media from the surface.…”
Section: Surface Finishing and Sterilizationmentioning
confidence: 99%
“…Specifically, sand blasted parts display surfaces with impregnated blast media in the form of AlO x elements -Al ions in the outer oxide layer of Ti-6Al-4V have been shown to reduce the oxide stability and increase the likelihood of Al ion dissolution [191,192] . Electropolishing and chemical etching can lead to the formation of micropits, increasing oxygen infiltration, as well as destabilize the native oxide layer, reducing corrosion resistance [191,195] . Conversely, Longhitano et al investigated the combination of various finishing processes on SLM Ti-6Al-4V, and found that blasting followed by chemical etching produced parts with and R a of approximately 4 µm -this can be explained by the stepwise action of blasting removing material from the surface, and subsequent etching removing blast media from the surface.…”
Section: Surface Finishing and Sterilizationmentioning
confidence: 99%
“…Independently on time of its use, the inter-operational model must be sterile and it is supplied into an operating room in an appropriate packing, with a description guaranteeing its use for appropriate patient [8]. Manufacturing a product in conditions, which are not sterile, sterilization should be ensured.…”
Section: Theoretical Informationmentioning
confidence: 99%
“…The structural fat graft now considered by many plastics surgeons Achieved that both reconstructive surgery and aesthetic surgery is accomplished easily. It is a valuable tool for soft tissue augmentation 40 O'Malley et al 85 AM technology is best suited for the fabricated implant of complex geometry and produced accurately Additive Manufacturing technology is suitable for medical devices and clinical environment designs implant used for patients which are less in number and differ from patient to patient. Additive manufacturing fulfils the need and products are quickly available and produced at an economical price.…”
Section: Applications Of Additive Manufacturing In Medicalmentioning
confidence: 99%